Fungal canker disease on Populus spp. in China caused by three species of Nothophoma including N. populi sp. nov. - Guo, Lin-Na; Wang, Jia-Wen; Zhao, Li-Li; Zhang, Lin; Zhang, Ying (Phytotaxa, 2025)
Diseases affecting branches and trunks of poplar trees (Populus spp.) cause severe damage in poplar cultivation areas within China. In this study, thirty-three poplar trunks and branches exhibiting canker symptoms were collected from Beijing and Ningxia provinces, China. Forty-three isolates of Nothophoma were obtained. Phylogenetic analysis, based on combined ITS, RPB2, and TUB2 DNA sequence data along with fungal morphological characteristics, identified three species of Nothophoma, namely N. populi, N. platycladus and N. juglandis. Of these, N. populi is a new species that is fully described. Koch’s postulates confirmed that all three species of Nothophoma can cause canker disease in poplar. This study is the first report of poplar diseases caused by species of Nothophoma.